Second Scope, New Findings: Pediatric Stridor Is Not Always Due to Croup or Laryngomalacia: A Case Report - Summer Ghaith; Deborah Hsu; William Dixon (Clinical Practice and Cases in Emergency Medicine)
Introduction: Infantile subglottic hemangioma is a rare and serious condition characterized by stridor, respiratory distress, and a barking cough. This condition poses a significant risk as it can lead to life-threatening airway obstruction. Case Report: We present a five-week-old patient who was diagnosed in the emergency department (ED) with moderate laryngomalacia via laryngoscopy by otolaryngology and discharged; he returned to the ED the next day with worsening symptoms of recurrent stridor, difficulty feeding, and worsening respiratory distress. A second laryngoscopic exam performed on the return ED visit revealed a subglottic mass that was later identified as a left-sided subglottic hemangioma via bronchoscopy and magnetic resonance imaging. The patient was treated with propranolol and discharged from the inpatient unit with dermatology and otolaryngology follow-up. Conclusion: Infantile subglottic hemangioma is a rare but serious cause of respiratory distress in infants, posing a risk of airway obstruction. This diagnosis should be considered in the ED, particularly for patients under two years of age, who present with recurrent stridor and respiratory distress and do not respond to standard treatments for croup.